Studying water-wedging as a cause for short term overheating in the boiler of a coal-fired power plant - Basson, Nicol (Department of Mechanical Engineering, 2019)
A common failure occurrence on fossil fuel power plant boiler systems is referred to as short term overheating (STO). This phenomenon occurs when the tube is heated to higher than its design temperature in a short period of time, causing a ductile failure of the tube material. The superheaters are particularly susceptible to STO. Such a failure can be caused by various conditions, where most of these are condition-based, i.e. based on the physical condition of the pipes or boiler. However, there are some cases which are process-related, i.e. based on the thermo-physical process occurring inside the pipe. Very often a water blockage or water wedge is recorded to be the root cause of the short term overheating in superheaters when no condition-based indicators can be found. It then is claimed to be the result of over-attemperation spray by the operator. This type of failure tends to happen at the outlet of vertical (pendant-type) superheaters. This study aims to find thermo-physical conditions where such a conclusion is valid by studying the transient behaviour of a representative superheater segment under postulated conditions. The specific geometry chosen is one for which short term overheating due to water wedging has been recorded in the past. A transient flow model was constructed and verified by comparing its results with plant data, as well as some results from a numerical model developed from fundamental principles. Once the simulation modelling methodology was confirmed, the model was modified to resemble the geometry of the final superheater outlet leg to facilitate direct comparison with a pendant boiler component as found on a power plant. A number of scenarios were executed in transient state on the model at different boiler loads. The temperature evolution of the pipe wall was tracked over time, and together with calculated equivalent stresses, was compared to the yield strength of the material. A temperature vs yield strength curve was obtained from material testing using new and aged tube material. The results showed that short term overheating at the superheater outlet tubes due to water blockages alone is unlikely to occur, even at low loads and substantial over firing. The stresses exerted over the tube wall and throughout the tube length is not enough to overcome the yield stress of the superheater tube material, even for aged material. Thus, the claim of overattemperation as the root cause of a short term overheating failure is improbable, and other explanations for the failure must be observed. Even though it is possible for water-wedging to occur, the phenomenon alone is unlikely to be the root cause for the occurrence of short term overheating.